Initiating an Educational Agricultural Flower Tourism Village through the Construction of Language Landscape and Eco Folklore - Wulandari, Badriyah; Rokhmawan, Tristan; Dewi, Aprilia Cintya (CV. Creative Tugu Pena, 2023)
The community service initiative seeks to elevate the educational tourism village by engaging in various activities, such as training in derivative product production, constructing branded landscape equipment, establishing an encyclopedia, and revitalizing folklore. Supported by the Directorate General of Higher Education, Research, and Technology, along with the Directorate General of Vocational Education through the 2023 PKM Grant Scheme, this initiative addresses multifaceted aspects of community development. Primarily, by training locals in derivative product production, the community gains the ability to craft handicrafts and enhance local products, creating economic opportunities and enhancing tourists' experiences. Simultaneously, the development of branded landscape equipment enhances the village's infrastructure, making it more appealing and comfortable for visitors while establishing a distinct identity. Moreover, the creation of an encyclopedia serves as a repository of local knowledge, history, and traditional wisdom. This not only informs tourists but also preserves cultural heritage for future generations. Lastly, the revitalization of folklore aims to bring oral traditions and storytelling back to life. Through folklore, local stories are presented in an engaging manner, enriching the educational tourism experience. These initiatives collectively result in an empowered, appealing, and culturally enriched tourism village. The economic upliftment, improved infrastructure, knowledge documentation through the encyclopedia, and cultural preservation through folklore contribute to the sustainable and positive development of the educational tourism village for all stakeholders. Keywords: Educational Tourism Village, Language Landscape, Eco-Folklore, Tuberose Flower